Case report: Treatment with Pien-Tze-Huang for prolonged positive SARS-CoV-2 test results in COVID-19 patients: A report of five cases - Zheng, Yujiao; Cheng, Jinbo; Gu, Chengjuan; Xiao, Mingzhong; Shao, Zuoyu; Zhao, Linhua; Tong, Xiaolin (Frontiers in Medicine, 2022)
As a global pandemic, Corona Virus Disease 2019 (COVID-19) has been rapidly spread around the world since December 2019. In the process of fighting against COVID-19, an atypical cases of COVID-19 which present with prolonged positive SARS-CoV-2 test results in the convalescence period appeared, which increased the difficulty of COVID-19 prevention and treatment. Here we report five cases of COVID-19 patients who underwent prolonged positive SARS-CoV-2 tests after regular TCM and western medicine treatments. Through giving Pien-Tze-Huang (PTH) and stopping previous treatments, the SARS-CoV-2 tests results of the patients have been totally turned negative. We believe the finding will contribute to a better understanding of the atypical COVID-19 cases and hope to offer a potential therapy. Since it’s a preliminary case series, larger-scale clinical trials are necessary to carry out.